Transition from Order to Configurational Disorder for Surface Reconstructions on SrTiO3(111) - Marks, L; Chiaramonti, A; Rahman, S; Castell, M (American Physical Society, 2015)
There is growing interest in ternary oxide surfaces due to their role in areas ranging from substrates for low power electronics to heterogeneous catalysis. Descriptions of these surfaces to date focus on lowtemperature explanations where enthalpy dominates, and less on the implications of configurational entropy at high temperatures. We report here the structure of three members of the n × n (2 ≤ n ≤ 4) reconstructions of the strontium titanate (111) surface using a combination of transmission electron diffraction, density functional theory modeling, and scanning tunneling microscopy. The surfaces contain a mixture of the tetrahedral TiO4 units found on the (110) surface sitting on top of octahedral TiO5½ (where [] is a vacant octahedral site), and TiO6 units in the second layer that are similar to those found on the (001) surface. We find clear evidence of a transition from the ordered enthalpy-dominated 3 × 3 and 4 × 4 structures to a configurational entropy-dominated 2 × 2 structure that is formed at higher temperatures. This changes many aspects of how oxide surfaces should be considered, with significant implications for oxide growth.